PKA‐independent vasopressin signaling in renal collecting duct. Issue 5 (26th March 2020) - Datta, Arnab; Yang, Chin‐Rang; Limbutara, Kavee; Chou, Chung‐Lin; Rinschen, Markus M.; Raghuram, Viswanathan; Knepper, Mark A.
Abstract: Vasopressin regulates renal water excretion by binding to a Gα s‐coupled receptor (V2R) in collecting duct cells, resulting in increased water permeability through regulation of the aquaporin‐2 (AQP2) water channel. This action is widely accepted to be associated with cAMP‐mediated activation of protein kinase A (PKA). Here, we use phosphoproteomics in collecting duct cells in which PKA has been deleted (CRISPR‐Cas9) to identify PKA‐independent responses to vasopressin. The results show that V2R‐mediated vasopressin signaling is predominantly, but not entirely, PKA‐dependent. Upregulated sites in PKA‐null cells include Ser256 of AQP2, which is critical to regulation of AQP2 trafficking. In addition, phosphorylation changes in the protein kinases Stk39 (SPAK) and Prkci (an atypical PKC) are consistent with PKA‐independent regulation of these protein kinases. Target motif analysis of the phosphopeptides increased in PKA‐null cells indicates that vasopressin activates one or more members of the AMPK/SNF1‐subfamily of basophilic protein kinases. In vitro phosphorylation assays using recombinant, purified SNF1‐subfamily kinases confirmed postulated target specificities. Of interest, measured IBMX‐dependent cAMP levels were an order of magnitude higher in PKA‐null than in PKA‐intact cells, indicative of a PKA‐dependent feedback mechanism. Overall, the findings support the conclusion that V2‐receptor mediated signaling in collecting duct cells is in part PKA‐independent.